PALLIATIVE CARE IN THE EMERGENCY DEPARTMENT: A SYSTEMATIC REVIEW. Issue 12 (18th November 2016) - Cooper, E; Sheikh, Z; Townend, W; Johnson, M; Hutchinson, A
Abstract : Objectives & Background: Emergency departments (EDs) receive a variety of patients: those with unexpected injuries or trauma, chronic disease exacerbation or progression and existing advanced disease or terminal illness. Thus expectations of attendees can vary greatly. However the primary focus of EDs is acute management.The provision of tailored palliative care (PC), that meets the unique needs of people with advanced disease, is often difficult in the ED. The main objective of this qualitative synthesis was to increase understanding of the ED experience of people with advanced disease, their relatives and healthcare professionals. Methods: Medline, Embase, CINAHL and PsychInfo were searched for articles published prior to 2016. All titles and abstracts were reviewed by two independent reviewers according to predefined eligibility criteria. Differences were resolved by discussion and recourse to a third independent reviewer. The subsequently identified full texts then underwent the same process. Included papers were appraised for quality. A thematic synthesis of these qualitative data was then conducted using the techniques described by Thomas and Harden. Results: The search identified 19 studies which fulfilled the inclusion criteria. All passed the quality appraisal stage. Coding of the articles revealed 31 free text codes which were divided into nine key themes: environmental factors, provision of care, communication, interdisciplinary working, decision making, accessing care, education, legal concerns and preparation for death. These were condensed further into three analytical themes that described the most prominent aspects of the experience of PC patients, relatives and healthcare providers in the ED: environment and purpose; systems of care and interdisciplinary working; education and training. Conclusion: This synthesis has provided a greater breadth of insight to enable recurring themes regarding the potential conflicts between emergency care and PC to be identified with a view to overcoming the challenges faced. Significantly recognising the need for educating ED physicians in the scope and components of PC, improving interdisciplinary working and enabling better understanding of patients and carers about their likely disease progression and the opportunities open to them. Further research should focus on the best ways to provide such education, the specific reasons for shortfalls in communication and how these could be overcome.